Mode-Expanded Bus Architecture for Non-Sensitive Waveguide Alignment in Vertically-Coupled Microring - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2006)
We demonstrate experimentally a five-fold improvement in fabrication tolerance for vertically-coupled microrings using a mode-expanded bus waveguide. The power coupling coefficient is observed to vary by only 6% for misalignment as high as 1um.